Burnout pada Mahasiswa yang Bekerja: Pembelajaran Selama Pandemi Covid-19 - Lovinda Lianti; Tantri Yanuar Rahmat Syah (Neolectura, 2023)
There have been significant changes brought about by the COVID-19 epidemic in all spheres of life, including labor and education. Since the government has enacted PSBB (Large-Scale Social Restrictions) rules, practically all community activities are now done at home. With an emphasis on their burnout rate, the author of this study wishes to investigate how students who work during the COVID-19 pandemic behave. Due to the detrimental effects that burnout has on both individuals and organizations, it is crucial to pay attention to it. In comparison to other students or professionals, working students are said to have higher job expectations and more sensitive emotional states. The purpose of this study is to ascertain how job demands affect burnout, how burnout affects work engagement and turnover intention, and how work engagement affects turnover intention. With 230 participants, this study used the structural equation model (SEM) analysis approach. According to the study's findings, job demands positively influence burnout, burnout positively influences turnover intention while negatively affecting work engagement, and work engagement negatively influences turnover intention. Students who worked during the epidemic still exhibit some of these habits now, including the decision to study while doing online job. The management conclusion that can be suggested in this situation is that colleges or organizations are recommended to develop regulations that are appropriate for working students and that take into account whether they want to study or work online or offline. Furthermore, it is advisable to take into account how much time it will take working pupils to complete tasks well before giving them. Lastly, develop a website or application.